Reproduction of Indian Mackerel Rastreliger kanagurta (Cuvier, 1816) in Morodemak Coast Demak Regency - Dwi Rachmanto; Djumanto Djumanto; Eko Setyobudi (Universitas Gadjah Mada, 2020)
Indian mackerel is a group of small pelagic fish that has high economic value and is ecologically important. The catch of Indian mackerel in the Morodemak Coastal Fishing Port of Central Java has decreased within 2016-2018, which is suspected by overexploitation. This study aims to observe the reproduction of Indian mackerel. Fish samples were collected from the catches of the mini purse seine operated by fishermen in April-June 2019. The fish samples were measured their length and weight individually, then the abdomen dissected to collect gonad, and counted in sub-sample of the egg number. Data were analyzed to determine the length-weight relationship of fish, sex ratio, gonad maturity level (GML), gonad maturity index (GMI), the size of the first gonad matured, and the egg number in each gonad brood fish. The results showed a negative allometric length relationship, and the length-weight relation equation in female fish was W = 0.038 L 2.59 and in male was W = 0.178 L 2.03. The value of fish condition factors in males, and females obtained values ranging from 1-2. The proportion of fish in GML III ranges from 27.2 to 82.5%, while GML IV ranges from 3.6 to 33.8%. Fish GMI ranged from 0.17 to 4.75%. The eggs number ranged from 11.235 to 40.878 grain. The female Indian mackerel get the first gonad matured at the size of 15.2 cm.